Last Glacial Maximum active layer thickness in Western Europe, and the issue of 'tundra gleys' in loess sequences. (9th June 2022) - Bertran, Pascal; Stadelmaier, Kim H.; Ludwig, Patrick
Abstract: Late Marine Isotope Stage (MIS) 3 and MIS 2 loess–palaeosol sequences in Western Europe comprise alternating loess layer and 3‐ to 30‐cm‐thick bleached soil horizons with Fe–Mn oxide precipitations, which are usually interpreted as waterlogged active layers and referred to as 'tundra gleys'. Active layer thickness data derived from a regional climate model simulation and the fossils (shells, earthworm granules) found in 'tundra gleys' argue against such an assumption. Most of these horizons better correspond to Fe‐depleted, slightly humic topsoil horizons or subsurface eluvial horizons and should be referred to as (incipient) Ag or Eg horizons. They formed during climate ameliorations associated with vegetation (cryptogams, herbs) development, possibly limited by long‐lasting snow cover. Strong mixing usually occurred in these horizons due to the activity of anecic earthworms and frost activity.